Shame, blame, and culpability : crime and violence in the modern state - Rowbotham, Judith; Muravyeva, Marianna; Nash, David (David S.) (Routledge SOLON explorations in crime and criminal justice histories, 2013)
This ground-breaking collection of research-based chapters addresses the themes of shame, blame and culpability in their historical perspective in the broad area of crime, violence and the modern state, drawing on less familiar territories such as Russia and Greece, not just on material from familiar locations in western Europe. Ranging from the early modern to the late twentieth century, the collection has implications for how we understand punishments imposed by states or the community today.Shame, blame and culpability is divided into three sections, with a crucial case stu.